Andragogical approach to postgraduate education preschool teachers - Дятленко, Наталія (Educological discourse, 2013)
The andragogical components in postgraduate pedagogical education are being analyzed at the article; the methods and ways which influence positively the increase of teachers' interest towards their own trajectory of education are being noted, helps to increase the professional rate and formulates the will to study during all life.